In search of happiness in a Malay hero's life - Hamdan, Rahimah; Md. Radzi, Shaiful Bahri (Center for Promoting Ideas, 2014)
This paper discusses the value of the happiness enjoyed by a Malay hero, Hang Tuah, the famous 15th century warrior of the Melaka Empire. As a Malay hero, Hang Tuah was admired for his wisdom, prowess and strength. He was the epitome of the ideal Malay to his people, especially in his undivided devotion to the King of Melaka. His heroism and greatness as the Admiral of Melaka was evident when he was able to promote the reputation of Melaka, making it famous throughout the world. However, towards the end of his life, he was willing to forgo his fame as the Admiral of Melaka and abandon the king, to whom he owed his loyalty, in pursuit of his dream of genuine happiness in knowing and loving his Creator. Hang Tuah’s action had a very great impact on the king of Melaka, until he also stepped down from the throne to follow after the action of Hang Tuah. It can be said that the absence of Hang Tuah to lead the attack against the Portuguese invasion in 1511 was the cause of the immense destruction of this Malay empire. One hypothesis that can be advanced is that the loss of Hang Tuah was most likely caused by an unbalanced happiness that led to his dissatisfaction with his life as the Admiral of Melaka. Based on this hypothesis, it can be suggested that Hang Tuah only possessed psychological rather than spiritual happiness during his time of service to the king of Melaka. Thus, a textual analysis of Hikayat Hang Tuah, as maintained by the renowned Malay scholar, Kassim Ahmad, will be conducted to identify the value of Hang Tuah’s happiness based on the perspective of Syed Muhammad Naquib al-Attas. The findings of this study indicate that Hang Tuah did not find a balance between the temporal and the hereafter in his search for happiness (sa'adah).